A novel method to detect hPG80 (human circulating progastrin) in the blood. Issue 38 (8th September 2021) - Cappellini, Monica; Flaceliere, Maud; Saywell, Veronique; Soule, Julien; Blanc, Emilie; Belouin, Fanny; Ortiz, Erika; Canterel-Thouennon, Lucile; Poupeau, Sophie; Tigrett, Sylvia; Vire, Bérengère; Liaud, Pierre; et al.
Abstract : hPG80 (human circulating progastrin) is produced and released by cancer cells and can be detected in the blood using DxPG80 ELISA kit. Abstract : hPG80 (human circulating progastrin) is produced and released by cancer cells. We recently reported that hPG80 is detected in the blood of patients with cancers from different origins, suggesting its potential utility for cancer detection. To accurately measure hPG80 in the blood of patients, we developed the DxPG80 test, a sandwich Enzyme-Linked Immunosorbent Assay (ELISA). This test quantifies hPG80 in EDTA plasma samples. The analytical performances of the DxPG80 test were evaluated using standard procedures and guidelines specific to ELISA technology. We showed high specificity for hPG80 with no cross-reactivity with human glycine-extended gastrin (hG17-Gly), human carboxy-amidated gastrin (hG17-NH2 ) or the CTFP (C-Terminus Flanking Peptide) and no interference with various endogenous or exogenous compounds. The test is linear between 0 and 50 pM hPG80 (native or recombinant). We demonstrated a trueness of measurement, an accuracy and a variability of hPG80 quantification with the DxPG80 test below the 20% relative errors as recommended in the guidelines. The limit of detection of hPG80 and the limit of quantification were calculated as 1 pM and 3.3 pM respectively. In conclusion, these results show the strong analytical performance of the DxPG80 test to measure hPG80 in blood samples.